A review of the application of fuzzy cognitive maps in the policy decision-making life cycle - Andreou, Andreas S.; Neophytou, Haris; Stylianou, Constantinos (My University, 2014)
Fuzzy cognitive maps are a qualitative modeling technique that uses expert knowledge to attempt to represent the interactions between problem-specific factors aiming to simulate how these interactions alter the factors and drive the current state of a problem to a different state. Recent years have seen an increase in the number of research attempts that propose the adoption of Fuzzy cognitive maps (FCMs) as a means to forecast the effect of a policy in a number of interesting domains, including land use, urban (re)development, and other social, political, or economic issues or to simulate the current state of affairs to pinpoint possible hotspots for creating a policy. This chapter presents an overview of these research attempts where fuzzy cognitive maps have been employed as a simulation tool in order to support decision makers in their assessment of the impact of policies and help them adopt the most suitable policy to implement.
Keywords: Fuzzy cognitive maps; FCM modeling